Analisis Tema Fantasi Keluarga di Kalangan Manusia Lanjut Usia (Studi pada Kelompok Posyandu Lansia di DKI Jakarta) - Kusumajanti Kusumajanti; Angela Efianda; Siti Maryam (CommLine, 2015)
This study was a long-term consideration of the Ministry of Social Affairs and communities in handling the problems of older persons (senior citizen) in Indonesia. Spe cific target of this research was to utilize themes of fantasy in each group meeting of the Elderly to be able to create cohesion among the group members. The research was using qualitative methods to analyze the family’s themes of fantasy in every story of the elderly. The data were obtained from observations of meetings and indepth interviews to members of the elderly and their families in the environtment. The research analyzed the themes of fantasy that often appeared in every meeting where the elderly like the theme of family and health. The stories were developed by using jokes and funny stories to create happiness and equality symbol on the family and health. The use of fantasy as a result of the reconstruc tion of consciousness embodied in various rhetorical fantasy of the past, to create cohesion among the group of seniors. This study showed that the cohesiveness as the strength of all the factors that encourage members to survive in the group.